MicroRNA-21-Enriched Exosomes as Epigenetic Regulators in Melanomagenesis and Melanoma Progression: The Impact of Western Lifestyle Factors - Melnik, Bodo C. (Cancers (Basel), 2020)
DNA mutation-induced activation of RAS-BRAF-MEK-ERK signaling associated with intermittent or chronic ultraviolet (UV) irradiation cannot exclusively explain the excessive increase of malignant melanoma (MM) incidence since the 1950s. Malignant conversion of a melanocyte to an MM cell and metastatic MM is associated with a steady increase in microRNA-21 (miR-21). At the epigenetic level, miR-21 inhibits key tumor suppressors of the RAS-BRAF signaling pathway enhancing proliferation and MM progression. Increased MM cell levels of miR-21 either result from endogenous upregulation of melanocytic miR-21 expression or by uptake of miR-21-enriched exogenous exosomes. Based on epidemiological data and translational evidence, this review provides deeper insights into environmentally and metabolically induced exosomal miR-21 trafficking beyond UV-irradiation in melanomagenesis and MM progression. Sources of miR-21-enriched exosomes include UV-irradiated keratinocytes, adipocyte-derived exosomes in obesity, airway epithelium-derived exosomes generated by smoking and pollution, diet-related exosomes and inflammation-induced exosomes, which may synergistically increase the exosomal miR-21 burden of the melanocyte, the transformed MM cell and its tumor environment. Several therapeutic agents that suppress MM cell growth and proliferation attenuate miR-21 expression. These include miR-21 antagonists, metformin, kinase inhibitors, beta-blockers, vitamin D, and plant-derived bioactive compounds, which may represent new options for the prevention and treatment of MM.